Don`t think about your movements: Effects of attentional instructions on rowing performance - Schücker, L.; Jedamski, J.; Hagemann, N.; Vater, H. (International Journal of Sports Science and Coaching, 2015)
The beneficial effect of adopting an external as opposed to an internal focus of attention during movement execution is well established for a range of motor tasks. As up-to-date findings in the field of endurance sports using physiological outcome measures are rare, the aim of this study was to examine attentional focus effects in rowing using oxygen consumption as the main dependent variable. Eighteen experienced athletes rowed three times eight minutes at a submaximum intensity on a rowing ergometer. For each of the three rowing blocks they had to adopt a different focus of attention which was on leg movement (internal), on a video (external) or without instructions (control). Results revealed an increase in in the internal focus condition compared with the external as well as with the control condition. We conclude that it is an internal focus that led to performance decrements rather than an external focus enhancing performance. The implications of these findings for application in practice are discussed. ABSTRACT FROM AUTHOR